Inhibition of Mayaro virus infection by bovine lactoferrin - Carvalho, Carlos A. M. (2014)
Universidade Federal do Rio de Janeiro. Instituto de Bioquímica Médica Leopoldo de Meis. Rio de Janeiro, RJ, Brasil.